B Hepatitis: Knowledge and Practical Approaches of Dental Students from UFPB - Luiz Felipe Fernandes GONÇALVES; Suennya Dantas dos SANTOS; Maria Sueli Marques SOARES; Caroline D'Fátima Santos de SOUSA; Angelinne Ribeiro ANGELO; Andréa Sarmento QUEIROGA (Association of Support to Oral Health Research (APESB), 2007)
Objective: To evaluate the knowledge and practical approachesof dental students from UFPB regarding B hepatitis.Method: 197 students from the 1st to the 10th semesters of theDental Course of the Federal University of Paraíba were enrolled inthe study. The students filled in a two-part questionnaire arguingabout: I) forms of prevention, routes of transmission and vaccinalscheme of B hepatitis; and II) use of individual protective equipment(IPE) and occurrence of occupational accidents. Students from the1st to the 4th semesters answered only the questions from part I,while the other students answered the questions from both partsof the questionnaire. Data were submitted to descriptive statisticsand chi-square test. P values <0.05 were considered significant.Results: 89.3% of the respondents affirmed to know the routes oftransmission and forms of prevention of B Hepatitis. Dental/medical/surgical procedures were the most often cited route of transmission(92.6%), while biosecurity was the most recognized form ofprevention (92%). 72.1% of the students had received the B hepatitisvaccine. However, only 50% presented a complete vaccinal schemeand only 9.95% had been tested for seroconversion after receiving3 doses of the vaccine. Occupational accidents occurred in 39students (33.3%) and only 17 (43.6%) received post-exposureprophylaxis. There was statistically significant difference (p=0.012)between the 5th-10th students and the 1st-4th students regardingtheir knowledge of B hepatitis.Conclusion: A high percentage of students from the surveyedpopulation were aware of routes of transmission and forms ofprevention of B hepatitis. However, an equally high percentage ofstudents had incomplete vaccinal scheme and were not tested forseroconversion after receiving 3 doses of the vaccine, beingtherefore vulnerable to B hepatitis.